2015
DOI: 10.1021/acs.orglett.5b02532
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Direct Photocatalytic C–H Fluorination for the Preparative Synthesis of Odanacatib

Abstract: Late-stage C-H fluorination is an appealing reaction for medicinal chemistry. However, the application of this strategy to process research appears less attractive due to the formation and necessary purification of mixtures of organofluorines. Here we demonstrate that γ-fluoroleucine methyl ester, an intermediate critical to the large-scale synthesis of odanacatib, can be accessed directly from leucine methyl ester using a combination of the decatungstate photocatalyst and N-fluorobenzenesulfonimide in flow. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 40 publications
1
91
0
5
Order By: Relevance
“…In this report, we applied a photocatalytic fluorination reaction (24,25,33) to rapidly produce and evaluate a series of fluorinated BCAAs as PET radiotracers. In vitro LAT affinity measured in CHO-K1 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we applied a photocatalytic fluorination reaction (24,25,33) to rapidly produce and evaluate a series of fluorinated BCAAs as PET radiotracers. In vitro LAT affinity measured in CHO-K1 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When necessary, resolution was performed by a 2-step N-acylation and enzymatic deacylation using porcine kidney acylase to yield the (S)-isomer of the BCAA according to Chenault et al (23). The BCAAs were fluorinated via a photocatalytic C-H fluorination procedure (24)(25)(26) as depicted below (Fig. 2) and described in the supplemental materials.…”
Section: Chemistrymentioning
confidence: 99%
“…Inspired by this advance, we considered the feasibility of using leucine (Leu (L)) as a native fluorination site in peptides. An examination of the literature revealed that Leu is uniquely susceptible to C−H abstraction and most commonly forms a carbon centered radical at the branched (isopropyl) position. In our hands, subjecting various amino acids (e.g., Glu (E), Lys (K), Arg (R), Phe (F)) to NaDT fluorination returned unreacted amino acid without degradation.…”
Section: Figurementioning
confidence: 99%
“…We have recently reported the direct fluorination of unactivated C−H bonds using the unique combination of a decatungstate photocatalyst and N ‐fluorobenzenesulfonimide (NFSI) . Considering our prior success in the fluorination of aliphatic,, acyl, and benzylic C−H bonds, we endeavoured to expand the reaction scope to include the fluorination of relatively weak pyridylic C−H bonds (4‐picoline BDE (CH 3 )≈87 kcal mol −1 vs. toluene BDE (CH 3 )≈90 kcal mol −1 ) . As a significant complicating factor, however, Crugeiras has reported that several amine bases react with NFSI at the sulfonyl group (and not the electrophilic fluorine) and decompose this reagent.…”
Section: Figurementioning
confidence: 99%